Distinct Functions and Assembly Mechanisms of Soil Abundant and Rare Bacterial Taxa Under Increasing Pyrene Stresses - Dong, Yuzhu; Wu, Shanghua; Deng, Ye; Wang, Shijie; Fan, Haonan; Li, Xianglong; Bai, Zhihui; Zhuang, Xuliang (Frontiers in Microbiology, 2021)
Elucidating the relative importance of the species interactions and assembly mechanisms in regulating bacterial community structure and functions, especially the abundant and rare subcommunities, is crucial for understanding the influence of environmental disturbance in shaping ecological functions. However, little is known about how polycyclic aromatic hydrocarbons (PAHs) stress alter the stability and functions of the abundant and rare taxa. Here, we performed soil microcosms with gradient PAHs stresses as model ecosystem to explore the roles of community assembly in determining structures and functions of the abundant and rare subcommunities. The dose-effect of PAHs significantly altered compositions of abundant and rare subcommunities. With increasing PAHs stresses, diversities increased in abundant subcommunities, while decreased in the rare. Importantly, the abundant taxa exhibited a much broader niche width and environmental adaptivity than the rare, contributing more to PAHs biodegradation, whereas rare taxa played a key role in improving subcommunity resistance to stress, potentially promoting community persistence and stability. Furthermore, subcommunity co-occurrence network analysis revealed that abundant taxa inclined to occupy the core and central position in adaptation to the PAHs stress. Stochastic processes played key roles in the abundant subcommunity rather than the rare subcommunity. Overall, these findings extend our understanding of the ecological mechanisms and interactions of abundant and rare taxa in response to pollution stress, laying a leading theoretical basis that abundant taxa are core target for biostimulation in soil remediation.